Practical handbook of photovoltaics : fundamentals and applications - Markvart, T.; Castañer, Luis (Elsevier Advanced Technology, 2003)
As part of the growing sustainable and renewable energy movement, the design, manufacture and use of photovoltaic devices is increasing in pace and frequency. The Handbook of Photovoltaics will be a 'benchmark' publication for those involved in the design, manufacture and use of these devices. The Handbook covers the principles of solar cell function, the raw materials, photovoltaic systems, standards, calibration, testing, economics and case studies. The editors have assembled a cast of internationally-respected contributors from industry and academia. The report is essential reading for: Physicists, electronic engineers, designers of systems, installers, architects, policy-makers relating to photovoltaics.